ANALISIS DAN PEMODELAN SISTEM INFORMASI MANAJEMEN ASET PADA STIKOM DINAMIKA BANGSA JAMBI (Studi Kasus : Peminjaman Aset Tetap) - Maria Rosario B (JURNAL AKADEMIKA)
The asset management of STIKOM Dinamika Bangsa is still considered as paper-based or not supported by the use of information technology. By using the information technology, the asset management of the data will be more effective and efficient. One of business activities related to the asset of STIKOM Dinamika Bangsa is the asset loaning to the needy. This study discuss about the analysis and the design of asset loaning at STIKOM Dinamika Bangsa Jambi that will supported by the information system. The tool used in this research is object oriented approach i.e UML (Unified Modeling Language) that consists of Use Case Diagram, Class Diagram and Activity Diagram. This study will produce a prototype that then can be developed into information system which can be used as decision making in asset management at STIKOM Dinamika Bangsa Jambi